2015
DOI: 10.1136/tobaccocontrol-2015-052383
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoke exposure and respiratory morbidity in young children

Abstract: Secondhand smoke exposure during the prenatal and postnatal periods is associated with increased respiratory morbidity in children. Opportunistic screening and targeted smoking cessation counselling for parents at child hospital admissions and well-child outpatient visits, as well as preconception smoking cessation counselling for future pregnancies, may be beneficial to protect the child from negative health impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
3
16
1
Order By: Relevance
“…Only 12.5% of the mothers smoked regularly prior to pregnancy and 2.3% continued to do so during their pregnancy. The authors did not examine the independent effects of smoking during pregnancy versus postnatally because of insufficient power to detect the differences [26]. An American study of 206 infants with severe bronchiolitis focused on tobacco smoke exposure and the severity of bronchiolitis (measured by low oxygen saturations), and reported that prenatal TSE was not significantly associated with lower oxygen saturation among infants hospitalized with bronchiolitis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Only 12.5% of the mothers smoked regularly prior to pregnancy and 2.3% continued to do so during their pregnancy. The authors did not examine the independent effects of smoking during pregnancy versus postnatally because of insufficient power to detect the differences [26]. An American study of 206 infants with severe bronchiolitis focused on tobacco smoke exposure and the severity of bronchiolitis (measured by low oxygen saturations), and reported that prenatal TSE was not significantly associated with lower oxygen saturation among infants hospitalized with bronchiolitis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Literature has previously shown that offspring secondhand smoke exposure was associated with an increase in admission of respiratory diseases by 2 years of age (Snodgrass et al, 2016). We found that PTS was associated with infant frequent URIs, but the infants with frequent URIs were not significantly associated with CG methylation level of LMO2, GSTM1 , or IL10 in umbilical cord blood DNA.…”
Section: Discussionmentioning
confidence: 99%
“…URTI in infants was defined as pediatrician-diagnosed common cold, cough, or throat infections during the first year of life. 23,27 Information about URTI was obtained by telephone interview at 3, 6, and 12 months postpartum follow-up. Mothers were asked whether and when their infant had seen a doctor since the last assessment.…”
Section: Urti Outcomementioning
confidence: 99%